Characteristics of the Dye-Sensitized Solar Cells Using TiO(2) Nanotubes Treated with TiCl(4) - Yang, Jun Hyuk (Materials (Basel), 2014)
The replacement of oxide semiconducting TiO(2) nano particles with one dimensional TiO(2) nanotubes (TNTs) has been used for improving the electron transport in the dye-sensitized solar cells (DSSCs). Although use of one dimensional structure provides the enhanced photoelectrical performance, it tends to reduce the adsorption of dye on the TiO(2) surface due to decrease of surface area. To overcome this problem, we investigate the effects of TiCl(4) treatment on DSSCs which were constructed with composite films made of TiO(2) nanoparticles and TNTs. To find optimum condition of TNTs concentration in TiO(2) composites film, series of DSSCs with different TNTs concentration were made. In this optimum condition (DSSCs with 10 wt% of TNT), the effects of post treatment are compared for different TiCl(4) concentrations. The results show that the DSSCs using a TiCl(4) (90 mM) post treatment shows a maximum conversion efficiency of 7.83% due to effective electron transport and enhanced adsorption of dye on TiO(2) surface.